AN ARCHITECT CAN BE A DA’I - Sarker, Kamal Uddin (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2011)
Islam is a religion with complete code of life where all functions of personal, social, national, and international are well defined with the holy Quran, Sunnah, Ijma’, Qiyas and the lifestyle of Muhammad saw and his followers of that time. A Muslim can not but follow the rules and regulation of his life. Moreover, it is ever modern and modern so forth, only need to cautious in implementation the adaptability of invention of science. Architecture is a structure which has been carrying history century to century as well as creating links between generation to generation. In this paper I have tried to show how can architecture reflect Islamic life, and how can an architect became da’i by his creation or design. Keywords: Islamic architecture, da’i, architect